Detection of asymptomatic carotid stenosis in patients with lower extremity arterial disease: development and external validations of a risk score - Poorthuis, MHF; Morris, DR; de Borst, GJ; Bots, ML; Greving, JP; Visseren, FLJ; Sherliker, P; Clack, R; Clarke, R; Lewington, S; Bulbulia, R; Halliday, A (Oxford University Press, 2021)
Background: Recommendations for screening patients with lower extremity arterial disease (LEAD) to detect asymptomatic carotid stenosis (ACS) are conflicting. Prediction models might identify patients at high risk of ACS, possibly allowing targeted screening to improve preventive therapy and compliance.